SYNTHESIS AND CHARACTERIZATION OF AN AMIDOXIME COMPOUND WITH BENZIMIDAZOLE MOIETY AND PH SENSING BEHAVIOR UNDER BASIC CONDITION IN METHANOL AND DMSO - Nahidur Rahman, Mohammad; Bhowmick, Rina Rani; Nurnabi, Mohammad; Islam Molla, Md. Ashraful (Journal of the Chilean Chemical Society, 2018)
An amidoxime containing 2-phenyl-1H-benzimidazole derivative, 4-(1H-Benzoimidazol-2-yl)-N-hydroxy-benzamidine, was synthesized by conversion of nitrile group of previously synthesized 2-(4-cyanophenyl)-1H-benzimidazole by treatment with hydroxylamine under alkaline solution. Characterization of both compounds was carried out by using UV-Vis, FT-IR, 1H NMR and 13C NMR, and mass spectroscopic technique. Its photophysical behavior was compared in methanol and DMSO under basic condition.